Characterization of the m6A regulators’ landscape highlights the clinical significance of acute myocardial infarction - Chao, Peng; Zhang, Xueqin; Zhang, Lei; Wang, Yong; Wusiman, Miriban; Aimaijiang, Gulizere; Chen, Xiaoyang; Yang, Yining (Frontiers in Immunology, 2024)
Objective: Acute myocardial infarction (AMI) is a severe cardiovascular disease that threatens the human life and health globally. N 6 -methyladenosine (m 6 A) governs the fate of RNAs via m 6 A regulators. Nevertheless, how m 6 A regulators affect AMI remains to be deciphered. To solve this issue, integrative analysis of m 6 A regulators in AMI was conducted.We acquired transcriptome profiles (GSE59867, GSE48060) of peripheral blood samples from AMI patients and healthy controls. Key m 6 A regulators were used for LASSO, and consensus clustering was conducted. Next, m 6 Ascore was also computed. Immune cell infiltration, ferroptosis and oxidative stress were evaluated. In vitro and in vivo experiments were conducted to verify the role of m 6 A regulator ALKBH5 in AMI. Results: Most m 6 A regulators presented notable expression alterations in circulating cells of AMI patients versus that of controls. Based upon key m 6 A regulators, we established a gene signature and a nomogram for AMI diagnosis and risk prediction. AMI patients were classified as three m 6 A clusters or gene clusters, respectively, and each cluster possessed the unique properties of m 6 A modification, immune cell infiltration, ferroptosis and oxidative stress. Finally, the m 6 Ascore was utilized to quantify m 6 A modification patterns. Therapeutic targeting of ALKBH5 greatly alleviated apoptosis and intracellular ROS in H/R-induced H9C2 cells and NRCMs. Conclusion: Altogether, our findings highlight the clinical significance of m 6 A regulators in diagnosis and risk prediction of AMI, and indicate the critical roles of m 6 A modification in regulation of immune cell infiltration, ferroptosis and oxidative stress.